2008
DOI: 10.7326/0003-4819-149-11-200812020-00007
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Review: Do State Laws Make It Easier to Say “I'm Sorry?”

Abstract: Initiatives intended to reduce the frequency and impact of medical errors generally rely on recognition and disclosure of medical errors. However, fear of malpractice liability is a barrier to physician disclosure. Some U.S. state legislatures have attempted to encourage physicians to disclose medical errors by enacting "apology laws." The authors reviewed the codified statutes of each of the 50 states and the District of Columbia to determine the prevalence and characteristics of such apology laws. They found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 16 publications
0
36
0
1
Order By: Relevance
“…While some studies (26,36) have suggested that disclosure of errors might actually reduce the chance that patients will sue, the actual effect of disclosure on litigation remains hotly contested. Many states have adopted "apology laws" to encourage disclosure, but the legal protections provided by most of these laws are minimal (21,37). Definitive research clarifying the relationship between disclosure and litigation would allow disclosure guidelines to be more firmly evidence based.…”
Section: Health Policy and Practice: Disclosing Harmful Mammography Ementioning
confidence: 99%
“…While some studies (26,36) have suggested that disclosure of errors might actually reduce the chance that patients will sue, the actual effect of disclosure on litigation remains hotly contested. Many states have adopted "apology laws" to encourage disclosure, but the legal protections provided by most of these laws are minimal (21,37). Definitive research clarifying the relationship between disclosure and litigation would allow disclosure guidelines to be more firmly evidence based.…”
Section: Health Policy and Practice: Disclosing Harmful Mammography Ementioning
confidence: 99%
“…40 Some lawmakers have attempted to encourage physician disclosure and apology by reducing this legal risk through legislative changes to the hearsay rule exceptions. 30,33,41 Many state legislatures have attempted to encourage disclosures and apologies by adopting "apology laws, " intended to encourage physician-patient communications about AEs by limiting, or even completely excluding, plaintiffs' ability to use such communications as evidence against the physician in later litigation. 30,41 "Sympathy-only" apology laws bar the use of physician expressions of sympathy by plaintiffs at trial to prove negligence but do permit plaintiffs to use physician statements that expressly admitted fault.…”
Section: Legal Risks Associated With Disclosure and Apologymentioning
confidence: 99%
“…30,33,41 Many state legislatures have attempted to encourage disclosures and apologies by adopting "apology laws, " intended to encourage physician-patient communications about AEs by limiting, or even completely excluding, plaintiffs' ability to use such communications as evidence against the physician in later litigation. 30,41 "Sympathy-only" apology laws bar the use of physician expressions of sympathy by plaintiffs at trial to prove negligence but do permit plaintiffs to use physician statements that expressly admitted fault. 30 On the other hand, "admission of fault" apology laws prevent plaintiffs from using virtually any previous physician disclosures to the patient and family, even when the physician admitted responsibility for an ME or other improper care, to prove negligence at trial.…”
Section: Legal Risks Associated With Disclosure and Apologymentioning
confidence: 99%
“…Many states have apology laws, but they vary. Some states like Colorado and Washington will protect an apology of fault [8], while others may protect an apology that expresses sympathy, but not fault. The drive behind these laws was to promote and protect open communication.…”
mentioning
confidence: 99%